Pengaruh Faktor Riwayat Lahir dan Sosial Ekonomi terhadap Gizi Lebih pada Remaja - Elita Oktorina Pasaribu; Drajat Martianto; Cesilia Meti Dwiriani (Media Kesehatan Masyarakat Indonesia, 2019)
Obesity is a major problem in the world, especially in adolescents whose prevalence increase and obesityin adolescents are multi-factorial desease. Birth history and socio-economic factors that influence obesity. Thepurpose of this study was to identify birth history and socio-economic factors for over nutrition in adolescents.The design of this study is a cohort study using secondary data from the Indonesian Family Life Surveys (IFLS)and carried out from December 2017 - August 2018. The study involved 426 adolescents aged 15-17 years. Thestatistical analysis used is Structural Equation Modeling (SEM). The direct effect on birth weight was gestationalage (OR 7.7) (p <0.05). The direct effect of adolescent nutritional status was found in father’s education (p <0.05)and maternal BMI (p <0.05) had a significant effect, while maternal education (p> 0.05), income / capita / month(p> 0.05 ), and the living area (p> 0.05) did not find significant results for over nutrition in adolescents. Adolescentswho have highly educated fathers and overweight or obese mothers are risk factor for adolescents to becomeover nutrition.